Avaliação dos fatores críticos para seleção e aplicação clínica dos pinos de fibra - Santos, Alana Beltran dos [UNESP] (2013)
Teeth that have lost much of its coronary structure need intraradical devices to achieve a desired retention of the restorative material, restoring aesthetics and function to the patient. For this purpose, several types of intracanal posts have been studied, where the fiber posts have great importance due to its increasing use in the dental market. The purpose of this study was to critically analyze published works and controversies encountered by various authors related to factors such as cementation, post surface treatment, and compression and fracture resistance, microleakage, diameter and length of the post, and the various materials used. A review of PubMed database, Bireme and Lilacs was performed using key words to get the largest number of items